Physicochemical Bedding Quality in Compost-Bedded Pack Barn Systems for Dairy Cows: A Systematic Review - Carlos Eduardo Alves Oliveira; Ilda de Fátima Ferreira Tinôco; Cecília de Fátima Souza; Fernando da Costa Baêta; Rafaella Resende Andrade; Frederico Márcio Côrrea Vieira; Matteo Barbari; Gianluca Bambi (Applied Sciences, 2023)
In this study, a systematic review was performed to describe and discuss the main results available in the literature on physicochemical bedding quality in compost-bedded pack barn (CBP) systems for dairy cows. Experimental peer-reviewed articles in English were searched in the Scopus (ScP) and Web of Science (WoS) databases. The resulting articles (n = 162) underwent an evaluation process in four stages, following the PRISMA methodology and, based on a priori-defined eligibility criteria, 12 were selected. Several indicators of bedding quality were used, emphasizing bedding temperature in the aerobically active layer, evaluated in all studies. The decomposition activity was less intense in winter due to mild environmental conditions. During this period, appropriate management practices should be used (more frequent bedding replacement and turning, use of aeration systems under the bedding, lateral closures in the facilities, etc.) to maintain the fully active composting process. In conclusion, the physicochemical bedding quality in this system type is mainly affected by environmental conditions. However, some care is needed to extrapolate these results since this is a recent research area, which still requires further studies.